Paradigma, ki bo spremenila tudi izobraževanje odraslih - Javrh, Petra (AS. Andragoška spoznanja, 2009)
Modern moment more and more denotes realisation that we will have to change the way of life in order to preserve this planet and culture for descendants. We talk about new paradigm relationship to the world and action, which can by its extent compete with other widest and biggest worldćs movements under UNESCO, World health organisation and other international organisations. Movement of endeavours for lasting development is defined and encouraged by series of international documents, accepted in last two decades. They are the result of countries' efforts and politics which acknowledge the necessity of active uniting of powers and resources, to preserve the planet and ensure future for generations to come. Important vision is a holistic development of a person who is becoming an active and responsible citizen, ready to co-influence important decisions. Usefulness and life knowledges, constructive, critical thinking and cooperation are those components which arenecessary for making these decisions and will lead to true long-lasting development. Therefore must be visions and values of lasting development also key component of quality education (UNESCO 2004) in the vertical and all others extensions, also in the lifelong dimension. Theorists predict - practitioners are already experiencing this - that education of adult will have to change innovatively in order to follow the requirements of this paradigm.
Keywords: sustainable development; trajnostni razvoj; izobraževanje odraslih; Lifelong learning; vseživljenjsko učenje